The optimization of torque ripple reduction by using DTC-multilevel inverter. (February 2022) - Tarusan, Siti Azura Ahmad; Jidin, Auzani; Jamil, Mohd Luqman Mohd
Abstract: Direct Torque Control (DTC) scheme introduces a robust and simple control of electrical drive. However, its shortcomings such as broad torque ripple and variable switching frequency have offered several improvements like Space Vector Modulation (SVM) strategy, multilevel inverter (MLI) topology, etc. The conventional DTC which is fed by the two-level inverter has limited voltage vector, results in some difficulties to optimize the operation, especially at low operating speed. In contrast to MLI, the abundant of voltage vector has provided various amplitudes and angles that can overcome the problem of conventional DTC. Thus, this paper introduces the selected optimal voltage vector obtained from five-level Cascaded H-Bridge (CHB) inverter that employs in DTC hysteresis-based to achieve better optimization that similar to the DTC-SVM. Initially, the research work begins with an investigation on the performance comparison between a DTC hysteresis-based between two-level inverter (conventional method) and a five-level CHB inverter (proposed method). Here, a DC generator acted as a load is employed to control the operating speed instead of the speed controller (speed controller is negligible). Hence, the DTC method is optimized by minimizing the torque ripple as well as retaining the torque control capability at constant torque region on several operating speed. The selected optimal vector from the look-up table DTC of five-level CHB inverter must be dynamically appropriate to any change of torque (increased or decreased torque). For simplicity, this paper will only discuss the experimental results for both topologies of drive system. From the experimental results, it is verified that the torque ripples by the proposed method have achieved 10% and 50% reduction at high and low operating speed respectively. It is found that the DTC hysteresis-based result simpler control method than DTC-SVM while maintaining similar output performance. Highlights: Five-level Cascaded H-Bridge (CHB) inverter is proposed in the DTC scheme. Optimal voltage vector is selected to analyze the torque performance on the several operating speeds. The torque performance on each operating speed is verified by using experimental test.